Autologous blood patching in the management of broncho-pleural fistula in spontaneous pneumothorax - Bivhusal Thapa (Society of Surgeons of Nepal, 2017)
Introduction: Autologous blood patching (ABP) has been described as a modality of treatment of bronchopleural fistulas (BPF). The success rates have varied chiefly because the numbers studied have been small and the populations inhomogeneous. We conducted this study to determine the success rate in patients with BPF of spontaneous onset.